Elevated Serum Alpha-Fetoprotein Is a Significant Prognostic Factor for Patients with Gastric Cancer: Results Based on a Large-Scale Retrospective Study - Zhan, Zhouwei; Chen, Bijuan; Yu, Jiami; Zheng, Jingxian; Zeng, Yi; Sun, Mingyao; Peng, Li; Guo, Zengqing; Wang, Xiaojie (Frontiers in Oncology, 2022)
Objectives To study the clinicopathological features and prognostic factors of serum alpha-fetoprotein (AFP) positive gastric cancer (GC). Methods: A cohort study including 2318 GC patients who underwent radical surgery from January 2008 to December 2015 was retrospectively analyzed. Patients were divided into two groups according to preoperative serum AFP values: 191 patients with AFP-positive GC (AFP>20ng/mL, 8.24%) and 2127 patients with AFP-negative GC (AFP≤20ng/mL, 91.76%). The clinicopathological features and prognostic factors were explored. Results: Compared with AFP-negative GC, AFP-positive GC had higher rates of liver metastasis, lymph node metastasis, venous invasion, and nerve invasion (all P<0.05). The 5-year OS, DFS and mLMFS of AFP-positive GC were shorter than AFP-negative GC (55.00% vs. 45.04%, P<0.001; 39.79% vs. 34.03%, P<0.001; 13.80 months vs. 16.25 months, P =0.002). In whole cohort, multivariate analysis found serum AFP levels (positive vs negative), pT stage, pN stage, nerve invasion (yes or no), venous invasion (yes or no) were independent prognostic factors. Serum AFP levels (20-300 ng/mL vs. 300-1000 ng/mL vs. >1000 ng/mL), pT stage, pN stage, venous invasion (yes or no) were independent prognostic factors in AFP-positive GC. Conclusion: Liver metastases and venous invasion are more likely to occur in AFP-positive GC and lead to poor prognosis. Serum AFP level is an independent prognostic factor in GC patients. As the level of AFP increases, the prognosis becomes worse.